FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PENCEGAHAN COVID-19 DI KABUPATEN LAMPUNG TIMUR TAHUN 2021 - Yusthin Meriantti Manglapy; Riska Safrida (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Cases and deaths due to Covid-19 continue to increase in East Lampung; It is closely related to Covid-19 prevention practices. This study aims to find out what factors are related to Covid-19 prevention in East Lampung District.An analytical observational study with a cross-sectional approach was conducted with 100 respondents aged ? 18 years domiciled in East Lampung District. The data is collected online using the KoBoToolbox platform shared through Instagram and Facebook. Variables were measured using questionnaires containing respondents' characteristics, Perception, Stigma, Prevention Practices, Knowledge, and WHOQOL-BREF questionnaires to measure the quality of life.The result showed that 57 % of respondents were male, 72 % were early adulthood, 67 % were employed, 54 % had an income ? IDR 2.432.150, 49 % of respondents had a practice score of ?42,58, 53% had a quality of life score ? 87, 60% had a perception score of ?43, 55% had a stigma score of ?62 and 64% had a ?28 knowledge score. Chi-Square test results show that factors related to the practice of Covid-19 prevention are gender, in which male is 2.6 times at risk of the practice with a score ?42.58. Preception ?43, 2.6 times at risk with a score ?42.58 and the quality of life ?87 with a score ?42.58, 2.2 more potentials in doing the practice.This research can be an input for policymakers to develop interventions and policies that are considered adequate for the community in Covid-19 prevention practices.Keywords : Perceptions, Quality of Life, Gender, Preventions, Covid-19